Where Czech meets math: Implicative-causal relations in mathematical word problems - Hirschová, Milada; Vondrová, Naďa (Bohemistyka, 2023)
The paper deals with the functioning of if-clauses in mathematical word problems and with their equivalents. First, the nature of a word problem as a text type is shown. Further, the difference between complex sentences with proper implicative-causal relation and a lay use of conditional clauses is examined. As its main goal, the paper presents a comparison of various instances of conditional clauses in mathematics word problems. Also, it shows the role of formulaic stereotypy and conventional assumptions in word problem texts as an integral part of both the mathematical and the communicative competence.